Ragam Qira’ah dalam Surat Qaf: Studi Kritis Tafsir Al-Jamī li Ahkām Al-Qur’an Karya Imam Al-Qurthubi dan Tafsir Muḥarrar Al-Wajīz Karya Imam Ibn Athiyyah - Nurmayanti, Lutfiya; AL Farizi, M. Syauqii Shalkhi (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
One of the factors contributing to the diversity of Qur'anic qira’ah (readings) is the difference in dialects among various Arab tribes, which led Prophet Muhammad (peace be upon him) to teach the Qur'an in accordance with the linguistic capabilities of his followers. This diversity did not end in that era alone but continued to attract the attention of scholars across generations. Consequently, a specialized discipline emerged to establish standards for the acceptance of qira’ah, aiming to prevent deviations. This study aims to critically examine the variations of qirāʾāt in Surah Qaf based on two classical tafsir works that extensively address the topic of qirāʾāt. The study employs a qualitative method by comparing the qirāʾāt variations in Surah Qaf from the perspectives of Tafsīr al-Jāmiʿ li Aḥkām al-Qur’ān by Imam al-Qurthubi and Tafsīr al-Muḥarrar al-Wajīz by Imam Ibn ʿAthiyyah. The findings indicate that both exegetes include not only mutawātir qirāʾāt (those with mass transmission) but also shādhdh qirāʾāt (irregular readings), accompanied by explanations for the differences. Furthermore, it is shown that al-Qurthubi tends to include more diverse qirāʾāt compared to Ibn ʿAthiyyah.